Mutational Analysis of the Varicella-Zoster Virus ORF62/63 Intergenic Region - Jones, Jeremy O. (American Society for Microbiology, 2006)
The varicella-zoster virus (VZV) ORF62/63 intergenic region was cloned between the Renilla and firefly luciferase genes, which acted as reporters of ORF62 and ORF63 transcription, and recombinant viruses were generated that carried these reporter cassettes along with the intact native sequences in the repeat regions of the VZV genome. In order to investigate the potential contributions of cellular transregulatory proteins to ORF62 and ORF63 transcription, recombinant reporter viruses with mutations of consensus binding sites for six proteins within the intergenic region were also created. The reporter viruses were used to evaluate ORF62 and ORF63 transcription during VZV replication in cultured fibroblasts and in skin xenografts in SCIDhu mice in vivo. Mutations in putative binding sites for heat shock factor 1 (HSF-1), nuclear factor 1 (NF-1), and one of two cyclic AMP-responsive elements (CRE) reduced ORF62 reporter transcription in fibroblasts, while mutations in binding sites for HSF-1, NF-1, and octamer binding proteins (Oct-1) increased ORF62 reporter transcription in skin. Mutations in one CRE and the NF-1 site altered ORF63 transcription in fibroblasts, while mutation of the Oct-1 binding site increased ORF63 reporter transcription in skin. The effect of each of these mutations implies that the intact binding site sequence regulates native ORF62 and ORF63 transcription. Mutation of the only NF-κB/Rel binding site had no effect on ORF62 or ORF63 transcription in vitro or in vivo. The segment of the ORF62/63 intergenic region proximal to ORF63 was most important for ORF63 transcription, but mutagenesis also altered ORF62 transcription, indicating that this region functions as a bidirectional promoter. This first analysis of the ORF62/63 intergenic region in the context of VZV replication indicates that it is a dual promoter and that cellular transregulatory factors affect the transcription of these key VZV regulatory genes.